CLOVE OIL FOR THE CONTROL OF FLACHERIE DISEASE AND ITS EFFECT ON ECONOMIC TRAITS OF SILKWORM, Bombyx moriL , LEPIDOPTERA; (MBICIDAE) - SUJATHA KUNTAMALLA; SAMPATH AKULA (International Journal of Pharma and Bio Sciences, 2015)
The effect of increasing doses of clove oil with anti-bacterial activity, nutritional parameters and economic traits of silkworm were studied. Clove oil was active against B.cereus and P. vulgaris at 1% and 5% concentrations.The experiments were carried through the larval period where it was noticed that the nutritional parameters increased significantly in the treated batches when compared to control and normal.The ECI and ECD were higher in T2 treated batches and a relatively high increase in economic traits suggest that clove oil has an impact on control of flacherie disease and also on the cocoon production.